MODERN TECHNOLOGIES FOR DEVELOPING STUDENTS’ ENGLISH VOCABULARY: MODERN TECHNOLOGIES FOR DEVELOPING STUDENTS’ ENGLISH VOCABULARY - Tuliboyeva, Nilufar; Balkibaeva (Журнал иностранных языков и лингвистики, 2025)
It is no secret that learning foreign languages has become a demand today. Nowadays, children of the independence period set themselves the goal of learning at least 2 foreign languages. For this, conditions have been created on a large scale in our homeland. Starting from the 1st grade, children begin to get acquainted with Russian and English. At the same time, the teaching of these languages continues until the 11th grade. During this process, students have the opportunity to master these languages at least to the (B1) level. In private schools and higher education institutions, German, French, Italian, Turkish, Arabic and other languages are additionally taught. Learning each language requires a certain process. For example, grammar and vocabulary are of great importance in learning a foreign language.